COPPER (Cu2+) REMOVAL FROM WATER USING NATURAL ZEOLITE FROM GEDANGSARI, GUNUNGKIDUL, YOGYAKARTA - Wahyu Wilopo; Septiawan Nur Haryono; Doni Prakasa Eka Putra; I Wayan Warmada; Tsuyoshi Hirajima (Journal of Applied Geology, 2015)
Development of indusrialization and urbanization not only increase economic growth but also contribute to the environmental degradation, especially contamination of heavy metals in water. In other side, there are many geological materials have capability to immobilize heavy metals. Therefore, the objective of this research is to know the maximum capacity of natural zeolite from Trembono area, Gunung Kidul regency to immobilize copper (Cu2+) from water and to understand their mechanism. This experiment was carry out by a batch test. The result showed that the maximum capacity of zeolite to immobilize Cu (qmax) is 63,69 mmolCu/kg Zeolite according to Langmuir adsorption equilibrium model. In addition, the capability to immobilize Cu will increases due to decreasing the grain size. The result of this research can be used as an alternative for waste water treatment, especially Cu. Keywords: Removal, copper (Cu2+), natural zeolite, Langmuir isotherm